FIST - RT Biofarm Son. Bhd. collaboration - M. M., Yusoff; Saifful Kamaluddin, Muzakir; Nurul Nadia, Abd Razak; Siti Maznah, Kabeb; Noor Suhana, Adzahar (Penerbit UMP, 2010)
Pekan, Jan 25- An on-site visit was held at RT FIST's team was met by RT Biofarm which was Biofa rm Sdn. Bhd. to initiate research led by PKNP's CEO, YH Dato Hj Lias Mohd Noor. collaboration with FIST's Industrial Biotechnology Program. RT Biofarm Sdn. Bhd. is a company that currently supplies chicken to AYAMAS Sdn. Bhd.